PENGARUH MEDIA SOSIAL TERHADAP MANAJEMEN JURNAL ILMIAH DI INDONESIA - Basri Basri; Nur Alim Djalil; Muhammad Asdar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
This study aims to measure the effect of using social media as a scientific communication feature on the management of scientific journals in Indonesia. This research was conducted as a form of communication research in scientific communication, especially in media management. The method used is through a qualitative approach. Observations were made with a focus on measuring the level of interaction, increasing accessibility, and the impact of using social media on national indexation (SINTA). The information collection was conducted through in-depth interviews with representatives of journal managers, social media associations, and scientific media practitioners to gain an in-depth understanding of their views and experiences related to the use of social media in the context of scientific journal management. The analysis results provide perspectives on journal managers' motivations, challenges faced, and recommendations for further development. In conclusion, social media management can be an effective strategy for managing journals, increasing visibility, and improving the quality of national indexation. This research provides a holistic insight into the positive potential of social media use in the context of scientific journals while providing an in-depth view of the critical issues that need to be considered by journal managers and relevant stakeholders.